The Application of Sulfated Glycosaminoglycans in Pathologies of Vitreomacular and Retinal Interfaces. Literature Review - I. D. Arsyutov; N. M. Kislitsyna; S. V. Novikov (Oftalʹmologiâ)
Perfection of technologies along with extreme diagnostic potential cause high clinical and anatomical effect of surgical intervention for vitreoretinal pathology. However final functional result is not always comparable with the prognostic expectations. Having the knowledge about the changes of the eye tissue at retinal pathology and their interrelation with the stages of healing in response to the operative trauma, it is possible to carry out timely preventive activity to optimize the healing process. Up to date the recognized method of treatment of resistant macular edema and increasing of visual acuity in patients is intravitreal injection of corticosteroids. However, their application is limited both in acute and distant period due to a wide range of side effects. Therefore, the problem of inhibition and complex treatment of traumatic effects on the retina in the course of surgical treatment remains topical. A promising direction in solving this problem is the study of the influence of sulfated glycosaminoglycans (sGAG) on the inflammatory response and repair processes of vitreomacular and retinal interface structures. The purpose of this study was to summarize the experience of experimental studies of the effect of sGAG preparations on pathological processes of various tissues to create a substrate for further studies of their application in the field of vitreomacular and retinal interfaces.